2017
DOI: 10.1038/ncb3608
|View full text |Cite
|
Sign up to set email alerts
|

MK2 phosphorylation of RIPK1 regulates TNF-mediated cell death

Abstract: TNF is a master proinflammatory cytokine whose pathogenic role in inflammatory disorders can, in certain conditions, be attributed to RIPK1 kinase-dependent cell death. Survival, however, is the default response of most cells to TNF stimulation, indicating that cell demise is normally actively repressed and that specific checkpoints must be turned off for cell death to proceed. We identified RIPK1 as a direct substrate of MK2 in the TNFR1 signalling pathway. Phosphorylation of RIPK1 by MK2 limits cytosolic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
167
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(171 citation statements)
references
References 50 publications
4
167
0
Order By: Relevance
“…In complex‐I, ligation of TNFR1 induces various types of RIPK1 ubiquitination, which plays an essential role in recruiting the IKKs (IKKα/β/NEMO) and subsequent transcriptional induction of NF‐κB‐dependent pro‐survival genes including c‐FLIP, A20, and cIAP2 . In addition, transient phosphorylation of RIPK1 at Ser 25 by IKKs prevents its dissociation from complex‐I, and suppresses its Ser 166 ‐autophosphorylation‐dependent association with FADD to initiate formation of complex‐II/necrosome which functions as transcription‐independent players in TNF‐induced cell death . The kinase activity of RIPK1 is required for activation of RIPK3 that plays an essential role in necroptosis induction .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In complex‐I, ligation of TNFR1 induces various types of RIPK1 ubiquitination, which plays an essential role in recruiting the IKKs (IKKα/β/NEMO) and subsequent transcriptional induction of NF‐κB‐dependent pro‐survival genes including c‐FLIP, A20, and cIAP2 . In addition, transient phosphorylation of RIPK1 at Ser 25 by IKKs prevents its dissociation from complex‐I, and suppresses its Ser 166 ‐autophosphorylation‐dependent association with FADD to initiate formation of complex‐II/necrosome which functions as transcription‐independent players in TNF‐induced cell death . The kinase activity of RIPK1 is required for activation of RIPK3 that plays an essential role in necroptosis induction .…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8]48 In addition, transient phosphorylation of RIPK1 at Ser 25 by IKKs prevents its dissociation from complex-I, and suppresses its Ser 166 -autophosphorylationdependent association with FADD to initiate formation of complex-II/necrosome which functions as transcription-independent players in TNF-induced cell death. 18,22,49,50 The kinase activity of RIPK1 is required for activation of RIPK3 that plays an essential role in necroptosis induction. 14,15 Thus, discovery of small molecules regulating RIPK1 phosphorylation provides a basic research tool and substantiates the overall importance of early cell death checkpoint controlling apoptosis and necroptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, during ripoptosome signaling in myeloid leukemia cells, p38MAPK has been shown to inhibit TNF expression, and inhibition of MK2 results in enhanced cell death of leukemia cells (59). It was subsequently shown that MK2 mediates an inhibitory phosphorylation of RipK1, which restricts ripoptosome induced cell death (60)(61)(62). Our results indicate that the phosphorylation of RipK1 in macrophages is dependent on MK2, and inhibition of MK2 results in augmentation of ripoptosome induced cell death, particularly on day 12 macrophages.…”
Section: Discussionmentioning
confidence: 99%